x+(x+1)=(x+2)-(x-1)

Simple and best practice solution for x+(x+1)=(x+2)-(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(x+1)=(x+2)-(x-1) equation:


Simplifying
x + (x + 1) = (x + 2) + -1(x + -1)

Reorder the terms:
x + (1 + x) = (x + 2) + -1(x + -1)

Remove parenthesis around (1 + x)
x + 1 + x = (x + 2) + -1(x + -1)

Reorder the terms:
1 + x + x = (x + 2) + -1(x + -1)

Combine like terms: x + x = 2x
1 + 2x = (x + 2) + -1(x + -1)

Reorder the terms:
1 + 2x = (2 + x) + -1(x + -1)

Remove parenthesis around (2 + x)
1 + 2x = 2 + x + -1(x + -1)

Reorder the terms:
1 + 2x = 2 + x + -1(-1 + x)
1 + 2x = 2 + x + (-1 * -1 + x * -1)
1 + 2x = 2 + x + (1 + -1x)

Reorder the terms:
1 + 2x = 2 + 1 + x + -1x

Combine like terms: 2 + 1 = 3
1 + 2x = 3 + x + -1x

Combine like terms: x + -1x = 0
1 + 2x = 3 + 0
1 + 2x = 3

Solving
1 + 2x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 2x = 3 + -1

Combine like terms: 1 + -1 = 0
0 + 2x = 3 + -1
2x = 3 + -1

Combine like terms: 3 + -1 = 2
2x = 2

Divide each side by '2'.
x = 1

Simplifying
x = 1

See similar equations:

| 3-t/6=7 | | C=81000+18x | | 11a+9a=4a+30 | | 5w^2-2w+3=0 | | x^2+18x+90x=0 | | (7t-3)-(3t+1)=-3(1-3t) | | -2-42=x | | 5.60+.25x=19.85 | | 45x-11=250 | | 2x^2+16x+5= | | x*x+12x+32=0 | | 5(3p-5)+4p=5p-6(p+4) | | 14*30b=-196 | | 176-0.8a=122+a | | 5x+2(3x-4)=80 | | 8x+4y=22 | | -17=v | | 3x+50i=18-5yi | | 45-11x=250 | | y-94=5(x-9) | | -4p-13p-p=-150 | | 4y-14=30 | | 14*30+b=-192 | | y-2=5(x+3)fory | | y-9=5(x+8) | | 175+15d=250 | | 61n=187 | | 81-16t^2= | | 33=9-y | | 4w+3=2(w+1)+2w | | 61n+3118=187 | | 81-16t^2=0 |

Equations solver categories